Utwory o matkach i córkach - Sylwia Karolak (Ksiegarnia Akademicka Publishing, 2021)
From a large group of Polish postmemory literary texts, the author distinguishes a group that is considered to be significant and separate: Rodzinna historia lęku by Agata Tuszyńska, Utwór o Matce i Ojczyźnie by Bożena Keff, Włoskie szpilki by Magdalena Tulli oraz Frascati by Ewa Kuryluk. All these works were written by women. There are stories about complicated, often difficult and painful relations between mothers and daughters. It is important that these mothers are Polish Jewesses and Holocaust survivors. Their daughters represent the “second generation”. Fathers are absent in the lives of their daughters for many reasons (divorce, death, journey). This absence enables dialogue between the mother and her adult child, which helps shape the identity of the daughter and create the story about the Holocaust experience – the most important caesura and trauma in the mother’s life.